Description of a new species and the karyotype of the cavernicolous millipede Pseudonannolene Silvestri and the karyotype of Pseudonannolene strinatti Mauriès (Diplopoda, Pseudonannolenida, Pseudonannolenidae) - Fontanetti, Carmem Silvia [UNESP] (Sociedade Brasileira de Zoologia, 1996)
Pseudonannolene tocaiensis, sp.n. is described from Brazil, São Paulo, Itirapina. The karyotypes of P. tocaiensis, sp.n. and P. strinatti Mauriès, 1974 are also presented, both species are found in cave environments. P. tocaiensis has 2n=20, XY and P. strinatti, 2n=16; it was not possible to observe the sex determination mechanism in the latter.
Keywords: Diplopoda; Pseudonannolene; cave millipedes; cytogenetic; millipedes